Overyielding in mixed forests decreases with site productivity. (19th January 2015) - Toïgo, Maude; Vallet, Patrick; Perot, Thomas; Bontemps, Jean‐Daniel; Piedallu, Christian; Courbaud, Benoit; Canham, Charles
Summary There is a rising interest in the role of species diversity in ecosystem functioning and services, including productivity. Yet, how the diversity–productivity relationship depends on species identity and abiotic conditions remains a challenging issue. We analysed mixture effects on species productivity along site productivity gradients, calculated from a set of abiotic factors, in two biogeographic contexts (highlands and lowlands). We compared the productivity of 5 two‐species mixtures (i.e. 10 cases of mixed species) with that of monocultures of the same species. Five main European tree species were considered: sessile oak (Quercus petraea Liebl.), Scots pine (Pinus sylvestris L.), European beech (Fagus sylvatica L.), silver fir (Abies alba Mill.) and Norway spruce (Picea abies (L.) H. Karst). Our data set was compiled from the 2006 to 2010 French National Forest Inventory data base and covers 2361 plots including pure and mixed stands. Overall productivity of mixtures in highlands, that is European beech–Norway spruce, European beech–silver fir and to a lesser extent, silver fir–Norway spruce, was found to be higher than expected from the productivity of corresponding monospecific stands. Overyielding was mainly due to European beech for the first two mixtures and to silver fir for the third one. No effect of mixture was found for sessile oak–Scots pine and sessile oak–European beech stands in lowlands. Overyielding of sessile oak mixed with Scots pine was not strong enough to significantly increase overall stand productivity. Overyielding of European beech was balanced by an underyielding of sessile oak. The mixture effect changed along site productivity gradients for six cases out of the 10 studied, with a stronger and positive effect on sites with low productivity. The magnitude of this change along site productivity gradients varied up to 89% depending on the tree species. Synthesis. The nature of species interaction in mixtures with regard to productivity changes with species assemblage and abiotic conditions. Overyielding is strongest when species grow in highlands on less productive sites. A negative link between mixture effect and site productivity was found, in line with the stress‐gradient hypothesis.